IMPLEMENTATION OF COOPERATIVE LEARNING MODEL USING TYPE OF NUMBER HEAD TOGETHER (NHT) ON MATERIAL OF SPECIFICATION AND CONCRETE CHARACTERISTIC, CERAMIC, AND ROOF-TILE FOR BUILDING CONSTRUCTION IN CLASS OF CONCRETE ENGINEERING CONCENTRATION SMK NEGERI 1 - Chichilya Kosmawanti; Revianti Coenraad (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
This research is based on the student’ learning outcome of building construction major which is relatively low at under minimum passing grade score 75. Students are toward to be silent, passive, and less in involving on learning process. By NTH learning including the cooperative activity, it is expected to be meaningful learning providing the worthy academic experience for students, and they can possess the active involvement in learning activity. The aim is to discover the learning outcome of students after applied the cooperative learning model using NTH type. The research employs the descriptive method in which the quantitative data is number or score obtained from student’s learning outcome. The research schedule started between September 2016 and October 2016 conducted in SMK-N 1 Palangka Raya. Students of Class X TKBB SMK-N 1 Palangka Raya is selected as research subject participated by 25 person using research instrument on student’s final learning outcome. Each equation in final test sheet is investigated to gain the valid test model by three figures consisting to two lecturer of Department of Building Engineering in University of Palangka Raya and a teacher of Class X TKBB SMK-N 1 Palangka Raya. Previously it is 60 equations of test sheet. The result of validity analysis by ratter, it is obtained at about 40 valid equations. The data analysis utilized the individual and classical passing grade. The research result depicted that the whole learning activity and student’s learning outcome has been complete from 1th to 8th meeting in which it experienced the downward and upward trend. On the first meeting to last meeting, the result has been collected at 60%, 58%, 77%, 78%, 81% for complete learning portion followed by 75%, 75%, 79%, 80,9%, 83,3% categorizing into passing grade status. Then these have been compared to the final test analysis that gained the passing grade result of student’s learning outcome at around 88 % and the achievement level at 76,1 % with complete status. In conclusion, the learning outcome level can be improved by implementing the cooperative learning model with NTH type on material of specification and concrete characteristic, ceramic, and roof-tile for building construction in Class X TKBB SMK-N 1 Palangka Raya at academic year 2016/2017.